Efektivitas Kegiatan Mapag Hujan Melalui Program Pengelolaan Sampah Terhadap Mitigasi Bencana Banjir Di Wilayah Kelurahan Cipamokolan (Jurnal Manajemen Kreatif dan Inovasi, 2024)
The Bandung City Government ordered after this long dry season to anticipate floods in the coming rainy season by carrying out several programs from the Rain Mapag Activities, one of which is a waste management program, which will be held from 9 October-31 October 2023. The Acting Mayor of Bandung invites all sub-districts Bandung City to participate in carrying out Rain Mapag Activities to Mitigate Flood Disasters. Including Rancasari Subdistrict, they also gave orders to participate in supporting this government program to all subdistrict employees under the leadership of Rancasari Subdistrict, one of which is Cipamokolan Subdistrict. Cipamokolan Subdistrict has participated in and participated in the Rain Mapag Activity through a program for cleaning rubbish and water channels, and sorting rubbish to waste management, after doing it for 1 month. The results of interviews and giving questionnaires to 10 respondents. Gober employees, have The change in value from before carrying out the waste management program at the Rain Mapag Activity to after doing it, that the value of the respondents increased to a positive thing from all the questions given amounting to 275 out of 220, and 932 out of 689 interview questions. Which means that the Rain Mapag Activity through the Management Program This waste management program in the Cipamokolan Subdistrict area will be effective in its implementation for 1 full month in October 2023, after the rainy season comes, there will be minimal flooding and the river will not overflow onto the main road.